How university endowments respond to financial market shocks : evidence and implications - Brown, Jeffrey R. (2014)
Endowment payouts have become an increasingly important component of universities' revenues in recent decades. We study how universities respond to financial shocks to endowments and thus shed light on a number of existing models of endowment behavior. Endowments actively reduce payouts relative to their stated payout policies following negative, but not positive, shocks. This asymmetric behavior is consistent with "endowment hoarding," especially among endowments whose current value is close to the benchmark value at the start of the university president's tenure. We also document the effect of negative endowment shocks on university operations, such as personnel cuts.